The sociology of Norbert Elias - Loyal, Steven; Quilley, Stephen (Cambridge University Press, 2004)
Provides a comprehensive and accessible introduction to the key aspects of Elias's work and applies an Eliasian approach to key topics in contemporary sociology such as race, class, gender, religion, epistemology and nationalism. This book is a major contribution to Elias studies and a valuable resource for students and scholars.